Implementasi Projek Penguatan Profil Pelajar Pancasila Melalui Kegiatan Keagamaan pada Siswa Kelas VIII di SMP N 3 Kalikajar Wonosobo - Husein Mahmud; Muhammad Yusuf Amin Nugroho; Sri Jumini (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to: (1) explore religious activities in the Pancasila Student Profile (P5) strengthening project; (2) examine the implementation of the P5 project through religious activities among Grade VIII students at SMP N 3 Kalikajar Wonosobo; and (3) identify supporting and inhibiting factors in the implementation process. The research adopts a quasi-qualitative approach, using theory to test or expand existing concepts. Data collection was conducted through observation, interviews, and documentation, followed by data reduction, presentation, and verification. The findings reveal that religious activities within the P5 project contribute significantly to shaping students' character and morals by instilling religious teachings and Pancasila values in everyday life. The project fosters faith, piety, and independence, reinforcing the core values of P5. Key supporting factors include the enthusiasm of the school community, educators' strong religious understanding, and positive role models. Additionally, religious environments like Islamic boarding schools and TPQ (Qur’anic education centers) support the project’s success. However, several challenges hinder its implementation, such as students' inability to attend Dhuha prayer due to time constraints, inadequate prayer facilities, limited parental engagement, and insufficient support from external parties or the government for the development of religious infrastructure. These findings emphasize the need for collaborative efforts between schools, families, and stakeholders to optimize the impact of religious activities within the P5 framework and foster students’ holistic development in line with national character education goals.